A histological evaluation of cellular response on bone regeneration scaffold - Dewi, Anne Handrini; Listyarifah, Dyah; Ardhani, Retno; Jansen, John (Majalah Kedokteran Gigi Indonesia, 2023)
Biocompatibility testing for a new implant material is necessary before clinical use. The materials for bone scaffolding must also go through biocompatibility tests both in vitro and in vivo. The purpose of this study was to compare different staining methods in histological preparations to assess the biocompatibility of the material to tissues. Twenty Wistar rats (n= 20), aged 4 months, males, weighing about 250-350 g were divided into 2 research groups, namely sub-cutaneous and bone implantation for 3, 14, and 30 days. The sample was a biodegradable material with gypsum and calcium carbonate as the basic ingredients. Histological stains were prepared in several ways using Hematoxylin Eosin (HE), Mallory, Toluidine Blue, Tartrate-resistant acid phosphatase polyclonal antibody (TRAP), and Chromogen 3,3 diaminobenzidine (DAB) after pre-performing a decalcification process with ethylenedinitril-o-tetra-acetic acid (EDTA). The observation was done using magnification ranging from 10X10 to 100X10 with a light microscope (Nikon eclipse E600) and OptiLab viewer. The results were displayed in the form of descriptions of images generated from different staining methods. Staining by the HE method is most often chosen because it is cheap and easy but the other staining methods such as Toluidine Blue, Mallory, and TRAP show better contrast. Tissue staining techniques with immunohistochemistry (DAB, VEGF) are used to evaluate cell and tissue responses by identifying specific proteins present.